“Producción de plántulas de tabaco habano (nicotiana tabacum) variedad pelo de oro utilizando diferentes proporciones de humus de lombriz desinfestado y no desinfestado en Juan Guerra” - Vidal Tafur, Jorge Andrés (2005)
The present thesis titled Production of plántulas of tobacco cigar (Nicotiana tabacum) variety hair of gold, using different proportions of decontaminated humus and not decontaminated in Juan War'', he/she has as objectives: To produce plántulas of tobacco using different proportions of humus and decontaminated floor and not decontaminated to obtain plántulas of tobacco, to Evaluate the agronomic aspects and morfológicos of the plántulas of tobacco and to Elaborate the cost of production of the treatments in study. This experiment was executed in the fields of the TOBACCO COMPANY OF THE EAST S. A. Located Geographically to a south Latitude of 6º 30 ', Longitude west of 79º 30 'andan Altitude of 330 m.s.n.m.m. with a Political Location: Sector Pacaya, District of Juan Guerra, County and Region San Martín. A Complete Design was used at random (D.C.A.) with 4 observations and 6 treatments. The results demonstrated that the best plántulas production was obtained with the treatment T s (60% humus without decontaminating + 40% is accustomed to decontaminated), to register bigger height (7,80 cm), growth radicular (12,56 cm), shaft diameter (4,62 mm), 1 weigh radicular (3,89 g) and there was not presence of gills in the root (Degree O). on the other hand the bigger than quantity of gills in the root registered in the treatment T 1 ( 100% is accustomed to without decontaminating) with an average of 16,75; likewise he/she was mushrooms like: Penicillium sp., Fusarium oxysporum, Aspergillus sp., Rhizopus sp., Pythium spp. and Trichoderma sp. Lastly the treatment with 60% humus without decontaminating + 40% is accustomed to decontaminated (T s) it registered the smallest cost for plántula with an average of S l. 0,047 new suns.